Studi Literatur Tentang Permainan Tradisional Bentengan dan Gobak Sodor dalam Konteks Pengembangan Motorik dan Sosial Siswa Sekolah Dasar - Ilmia Qurrota Nisa'; Rif’at Hanim Zen; Laila Tussifa; Anissahrotul Hidayah (Lembaga Pengembangan Kinerja Dosen, 2025)
In the digital era like today, traditional games such as forts and gobak sodor are increasingly marginalized, even though these two games have great potential in supporting the motor and social development of elementary school children. This literature study aims to analyze the role of these two games in honing students' gross motor skills through running, jumping, and coordination activities, as well as social skills such as cooperation, communication, and sportsmanship. This research method uses a literature study with several stages, namely the data collection stage, the classification stage, the analysis stage, the synthesis stage, and the interpretation stage of relevant sources. The results of the study indicate that forts and gobak sodor are effective in training children's gross motor skills through dynamic movements such as running and dodging, while developing children's social values ​​through team interaction and collaborative strategies. Integration of traditional games in Physical Education learning in elementary schools can be a holistic strategy to improve students' physical and character development. The suggestion for educators is to modify these games so that they remain relevant to the current context without eliminating their educational value.